Impact of Vitamin D supplementation on Heart Rate Variability in Vitamin D deficient Asthma COPD Overlap Syndrome patients: A Randomized Controlled Trial - Nahar, Salsa Bill; Ferdousi, Sultana; Sultana, Shamima; Bennoor, Kazi Saifuddin; Rahman, Mustafijur; Khan, Mohammad Abdus Shakur; Hassan, Samia; Mahmood, Maksuda Binte; Rosy, Sharkia Khanam; Sultana, Nazneen; et al. (Journal of Bangladesh Society of Physiologist, 2020)
Background:Vitamin D3 deficiency is common in Asthma COPD overlap syndrome (ACO) and administration of vitamin D3 increased heart rate variability in healthy subjects. Objective: This randomized clinical trial aimed to investigate the therapeutic effect of vitamin D3administration on time domain measures of heart rate variability in 51 male vitamin D3(<30- 10ng/ml) deficient ACO patients. Methods: Patients were given either vitaminD3 capsule or placebo per week orally for 3 months and serum vitamin D3 level and time domain parameters of heart rate variability were assessed before and after the intervention. For statistical analysis, independent and paired sample t test was used. Results: Before intervention, vitamin D3 level and time domain parameters of heart rate variability were similar in all patients but these outcome measures significantly increased in vitamin D3 treated but not in placebo treated patients after 3 months. Conclusion:In conclusion, vitaminD3therapy is effective to improve heart rate variability in vitamin D3 deficient Asthma COPD overlap syndrome. J Bangladesh Soc Physiol. 2020, December; 15(2): 98-107